2016
DOI: 10.1038/nrc.2016.27
|View full text |Cite|
|
Sign up to set email alerts
|

New frontiers in translational control of the cancer genome

Abstract: The past several years have seen dramatic leaps in our understanding of how gene expression is rewired at the translation level during tumorigenesis to support the transformed phenotype. This work has been driven by an explosion in technological advances and is revealing previously unimagined regulatory mechanisms that dictate functional expression of the cancer genome. In this Review we discuss emerging trends and exciting new discoveries that reveal how this translational circuitry contributes to specific as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
333
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(346 citation statements)
references
References 253 publications
(295 reference statements)
10
333
0
3
Order By: Relevance
“…The oncogenic translation program of tumors is supported by aberrant activation of ribosome biogenesis and dysregulation of the translation initiation machinery (810). Here, we report the correlation between MYC activation and the translation of an oncogenic program in MM, which can be inhibited by the rocaglate derivative CMLD010509.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oncogenic translation program of tumors is supported by aberrant activation of ribosome biogenesis and dysregulation of the translation initiation machinery (810). Here, we report the correlation between MYC activation and the translation of an oncogenic program in MM, which can be inhibited by the rocaglate derivative CMLD010509.…”
Section: Discussionmentioning
confidence: 99%
“…Although ribosome biogenesis and translation initiation complex function have historically been perceived as passive processes, recent studies have revealed that they are actively regulated to support specific translation programs (8, 9). Here, using a proteome-wide approach, we report that targeting translation initiation in MM selectively depletes multiple oncoproteins while leaving other housekeeping proteins largely unperturbed.…”
Section: Discussionmentioning
confidence: 99%
“…In neurons, they are often involved in the regulation of synaptic function and plasticity. Unique features of these mRNAs remain controversial, because some groups have suggested that they have long and highly structured 5′UTR, whereas others found the presence of 5′ terminal oligopyrimidine tracts (5′TOPs) [23] and cis -regulatory elements [20,2426]. There is now strong evidence linking mTORC1 and MAPK activity to translation regulation and the sensitization of nociceptors and/or dorsal horn neurons that receive nociceptive input.…”
Section: Regulation Of Mrna Translation Via Eif4f Complex Formationmentioning
confidence: 99%
“…Another example of non-oncogene addiction is the reliance on translation factors. Cancer cells are dependent on the translational machinery for both global elevation of protein synthesis, as well as the translation of specific mRNAs that promote tumor survival[2]. The first observation indicating that regulators of mRNA translation are key facilitators of cancer cells is more than a century old, when prominent nucleoli, reflecting increased ribosome production to meet enhanced protein synthesis demands, were recognized as a morphological hallmark of cancer[3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both enhanced expression or activity of proteins involved in translation[7] and uncoupling of translation inhibition from tumor cell stressors (e.g., hypoxia, nutrient deprivation) are commonly observed in cancer[8]. In the past years, we have gained a vast body of knowledge on what specific changes occur in the translational machinery in cancer cells[7] and, although still in its infancy, the field of targeting translational control beholds great promise for anti-cancer drug development[2]. …”
Section: Introductionmentioning
confidence: 99%